Building a Qur'anic Paradigm - Mahwiyah; Ayyas Sabilul M; Early Fitriyani; Niken Princess Liana (Penerbit Hellow Pustaka, 2023)
This Qur'anic paradigm is very important for modern life because as you already know that the Qur'an for Muslims is primary guide and resource in all areas of life. Well, the Koran itself directs us to walk on the shirathal mustaqiim interpreted as a way straight God SWT so that Then We can end task life in a manner husnul khatimah. So, we as humans are required to make the Qur'an the solution to all life's problems. Al-Qur'an for people Islam is source primary in all facet life. The Qur'an is a source of teachings on theology, law, tasawuf, thought, reform, education, morals and other aspects. No only that, the Qur'an is also a benchmark of right or wrong, good or bad, And beautiful or Bad. In the end, the Qur'anic paradigm is in line with the goals of Islamic education, namely worshiping Allah SWT (QS Al-Dzariyat: 56). In other words, the Qur'anic paradigm must create Muslim individuals who believe and fear of Allah SWT who can lead people to achieve inner happiness the life of this world and the hereafter